Efek Klonidin Sebagai Ajuvan Anestesi Spinal Terhadap Kadar Glukose Darah - Prasetyo, Ahmad Helmi (Jurnal Kedokteran Indonesia, 2011)
Background: Stress response to post-surgical pain can raise blood sugar level. Excessive blood sugarlevel (hyperglycemia) in turn may increase the risk of mortality. Intrathecal morphine as a spinalanesthesia adjuvant has shown effective to suppress blood sugar increase. However, morphine caninduce serious adverse effects such as respiratory distress. This study aimed to determine the effectof Clonidine as a spinal anesthesia adjuvant on blood glucose level and duration of analgesia.Methods: A randomized controlled trial was conducted in 30 patients undergoing lower abdominalsurgery with spinal anesthesia. The patients were randomly divided into 2 groups. The control groupwas given an anesthetic agent 12.5 mg of 0.5% Bupivacaine and 0.3cc 0.9% NaCl. The experimentalgroup was given anesthetic agent 12.5 mg of 0.5% Bupivacaine and Clonidine 1mcg/ kg body weight.The primary outcome variable under study was blood glucose level before incision up to 12 hours afterthe end of operation. The side outcome variable was duration of analgesia. The effect of Clonidine wasreported in terms of OR, ARR, RRR, and NNT.Results: The addition of Clonidine to Bupivacaine 0.5% spinal anesthesia stabilized blood glucose level.Statistically significant lower level of blood glucose was demonstrated in subjects with Clonidine thanthose without Clonidine during the wound closure (p<0.024) and 12 hours after wound closure (p<0.040)of the surgery. Subjects receiving Clonidine showed 1/3 lower risk of hyperglycemia than those withoutClonidine (OR= 0.31; p=0.196). Addition of Clonidine decreased the risk of hyperglycemia as much as20% (ARR= 20.0%). Administration of Clonidine as an adjuvant effectively prevented the risk ofhyperglycemia (NNT= 5). Clonidine also prolonged analgesic duration (p<0.001).Conclusion: Clonidine is a desirable spinal anesthesia adjuvant as it provides stability to blood glucoselevel and lengthens analgesic duration. It can be used as an alternative to avoid the complicationsresulting from administration of opioid morphine as an adjuvant in a spinal anesthesia.Keywords: Clonidine, surgical stress, blood glucose